Developing an industry 4.0 tool based on a decision support system for the electricity sector - Domingues, Nuno (2022)
Industry 4.0 brings together disruptive technologies and methods such as Big Data, Advanced Analytics, Cloud Computing and Internet of Things IoT and means connecting devices, machines and equipment to the internet, interacting with each other and transforming static objects into dynamic elements of an integrated network. The basic foundation of Industry 4.0 in the electrical sector is that through the interconnection of machines, production systems and equipment, companies will have the ability to create intelligent networks along the entire value chain, and thus control and command the production processes independently. The Decision Support System (DSS) described in the present paper simulates an electric system regarding the technical, environmental, social and economical aspects. The DSS is based on a conceptual model that could be adapted for most Countries. The DSS helps to understand the effect of consumer practices, production technology and Government measures on the electricity sector. Computer-based systems are useful to deal with great amount of information. Also, computer-based systems are adequate to organize disperse information. The author developed a DSS based on informatics technologies and applied to showcases and scenarios that can be used for better decision-making.